Antitumor properties of a vanadyl(IV) complex with the flavonoid chrysin [VO(chrysin)2EtOH]2 in a human osteosarcoma model: the role of oxidative stress and apoptosis - Leon, Ignacio Esteban (2013)
Flavonoids, a polyphenolic compound family, and the vanadium compounds have interesting biological, pharmacological, and medicinal properties. We report herein the antitumor actions of the complex [VO(chrysin)2EtOH]2 (VOchrys) on the MG-63 human osteosarcoma cell line. Oxovanadium(IV), chrysin and VOchrys caused a concentration-dependent inhibition of cell viability. The complex was the strongest antiproliferative agent (p < 0.05). Cytotoxicity and genotoxicity studies also showed a concentration effect. Reactive oxygen species (ROS) and the alterations in the GSH/GSSG ratio underlie the main mechanisms of action of VOchrys. Additions of ROS scavengers (vitamin C plus vitamin E) or GSH to the viability experiments demonstrated beneficial effects (p < 0.01). Besides, the complex triggered apoptosis, disruption of the mitochondria membrane potential (MMP), increased levels of caspase 3 and DNA fragmentation measured by the sub-G1 peak in cell cycle arrest experiments (p < 0.01). Collectively, VOchrys is a cell death modulator and a promissory complex to be used in cancer treatments.